Access to the University of Malaya - Ungku Abdul Aziz, Ungku Abdul Hamid (UNESCO, 1972)
In a developing country, a university has the supreme task of preparing the leadership that is well equipped with adequate knowledge, practical experience and the right outlook to transform the society from a colonial semi-feudal system into a modern industrialized nation. Therefore, a fair method of selecting the applicant for admissions is essential to get correct applicants for revolutionizing the nation. This study is divided into five chapters. The first chapter is the introductory chapter. It describes the scope, terminology and the methodology used in preparing the study. The second chapter deals with the national setting of the University. A picture is given of the historical trends in the flow of school pupils towards the University. These trends are examined quantitatively and qualitatively. A picture is sketched of the current administrative, economic and constitutional setting within which the University must operate. Chapter III examines the relationship between different authorities in the University and how variations in its capacity to admit students can be made. The growth of the University budget and staff during the past decade form a background to a more detailed study of the pattern of expenditure in 1970. Student/staff ratios are an important topic in this chapter. Chapter IV provides a picture, in profile, of the routes and culs de sac that lies between the first year of primary education and university graduation. ROSS or the “Rank Order System of Selection” which has a considerable impact on access to certain faculties is the final topic. Chapter V describes the administration of admissions and the criteria for selection to the respective faculties. Data for recent years are provided to illustrate the actual processes involved. Chapter VI describes the four main sources of tension that cloud over the access route to the University. These are the four imbalances: academic (i.e. Arts/ Science route); urban bias; the new role of the Malaysian language and the rectification of apparent ethnic discrimination. Chapter VII examines all types of scholarships and loans that are awarded to undergraduates. Chapter VIII attempts, briefly, to draw certain tenuous conclusions regarding the relationship between access and graduate employment. The main hypothesis is that while planning the development of the university, the administrator should be rational and responsive to national needs for economic, social and cultural development. The present supply of graduates is so small in relation to total effective national requirements. The problem of the graduate unemployment has not yet arisen at the present moment. There is no evidence of an unemployed graduate community in any field. Nevertheless, this cannot be an excuse for weakness in planning for complacency.